FLAXSEED OIL ALONE AND AS AN ADJUVANT WITH PHENYTOIN IN MES-INDUCED SEIZURES IN ALBINO RATS - Damodar, Rahul H; Reddy, Suneel Kumar; Goyal, Malvika; E, Pradeep B (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study to evaluate the anticonvulsant activity of flaxseed oil alone and as an adjuvant to phenytoin sodium. Methods: A total of 24 albino rats were used for this study. Four groups - control, standard (phenytoin sodium), test (flaxseed oil), and flaxseed oil along with phenytoin were made with six rats in each group. Maximal electroshock seizures 60-Hz AC of 150 mA intensity for 0.2 s were induced using an electroconvulsiometer with ear electrodes 60 min after oral drug administration. Duration of tonic hind limb extension (THLE) in seconds was used as a measure of seizures induced. Results: The mean duration of THLE in 4 groups was 11.66 (Group I), 5.67 (Group II), 3.85 (Group III), and 2.69 (Group IV). Duration of THLE was reduced in flaxseed oil group (P < 0.000) compared to both control and standard. Other parameters such as regain of righting reflex and recovery time also showed improvement. The group where flaxseed oil was used as an adjuvant to phenytoin also showed significant anticonvulsant activity. It showed a greater reduction in the parameters compared to either drug alone. Conclusion: The study showed that flaxseed oil possesses marked anticonvulsant activity when used alone and as an adjuvant to phenytoin. This study shows the potential of flaxseed oil in generalized tonic-clonic seizure.